(untitled) (Journal of Health Sciences, 2022)
Introduction: Venipuncture has been practiced for centuries and is still one of the most common invasive procedures in health care. However, practice varies considerably between countries and between institutions and individuals within the same country. The purpose of this study was to examine the association between nurses’ clinical performance and the level of pain and anxiety experienced by children during venipuncture procedures.Methods: Participants were conveniently enrolled in this prospective cross-sectional study, the pain and anxiety levels of 400 children aged 6-12 years old were measured and correlated with measurements of clinical performance by 20 nurses during the venipuncture procedure. A major pediatric hospital in Iraqi Kurdistan recruited patients for 3 months between September 2019 and August 2020.Results: The study found that there was no statistically significant difference in the overall clinical performance of male and female nurses or between those who worked in different departments. However, nurses with a higher level of education, whether working in the public or private sector, had higher levels of clinical performance. The level of pain and anxiety of children during venipuncture decreased significantly in relation to increased levels of nurse performance (r-values: −0.137 and −0.137), which included both their pain-related performance (r-values: −0.224 and −0.229) and their anxiety-related performance (r-values: −0.177 and −0.204; p < 0.0001). The factors contributing to higher levels of clinical performance by the nurses during venipuncture procedures were a higher level of education, sufficient sleep and working in the medical department, being older in age, and having longer clinical experience.Conclusions: This study highlights that children’s pain and anxiety decreased when nurses’ clinical performance levels increased. The levels of pain and anxiety in the children were significantly decreased in those patients who received better clinical treatment from nurses during the venipuncture procedure.